Microwave-Assisted Synthesis of Ag Incorporated MgWO4 Composites by Solid-State Metathetic Approach - Sung Lim, Chang (Asian Journal of Chemistry, 2011)
A solid-state metathetic (SSM) route assisted by microwave irradiation was used to synthesize the Ag incorporated MgWO4 composites in 10 min under environmentally friendly conditions. The crystallized Ag incorporated MgWO4 composites were formed at 600 ºC for 3 h, showing a fine and homogeneous morphology with sizes of 0.5-1 μm. The synthesized Ag incorporated MgWO4 composites were characterized by scanning electron microscopy, energy-dispersed X-ray spectroscopy and Fourier transform infrared spectroscopy. The optical properties were investigated by photoluminescence emission and Raman spectroscopy.